2010
DOI: 10.1007/s11145-010-9247-x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting vocabulary, phonological awareness and concept about print among children at risk for learning disability: can e-books help?

Abstract: The purpose of the present study was to investigate the effect of activity with an educational electronic book (e-book), as compared with adult reading of the printed version of the same book, on the vocabulary, phonological awareness as well as concept about print of preschool children at risk for learning disabilities. The study involved the participation of 110 children aged 5-7. All participants were identified as having developmental delays placing them at risk for learning disabilities. The sample was ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 63 publications
5
69
0
3
Order By: Relevance
“…These results may be driven by the numeracy questions that are strongly associated with early numeracy, and via its effect on phonological awareness also by the home literacy environment part of the questionnaire. Note, however, that home literacy activities tend not to predict phonological awareness (e.g., Sénéchal & LeFevre, 2002), although recent studies on e-books show otherwise (Shamir, Korat, & Fellah, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…These results may be driven by the numeracy questions that are strongly associated with early numeracy, and via its effect on phonological awareness also by the home literacy environment part of the questionnaire. Note, however, that home literacy activities tend not to predict phonological awareness (e.g., Sénéchal & LeFevre, 2002), although recent studies on e-books show otherwise (Shamir, Korat, & Fellah, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…Computer-based programs have improved phonological awareness skills (Lonigan, Phillips, Cantor, Anthony, & Goldstein, 2003;Segers & Verhoeven, 2004) and vocabulary (Segers & Verhoeven, 2003). Interactive electronic books have been used to teach early language and literacy skills, including vocabulary, to young children (Shamir, Korat, & Fellah, 2010;Verhallen & Bus, 2010;Verhallen, Bus, & de Jong, 2006). Verhallen et al (2006) reported that children learned more vocabulary from multimedia, interactive storybooks than from static versions.…”
Section: Story Friends Interventionmentioning
confidence: 99%
“…This newer type of interaction seemed to increase children's engagement because they were experiencing more enjoyable activity, gaining more confidence and becoming less anxious. Apart from these studies, there are several other studies investigating efficacy of e-books with respect to children's emergent literacy (such as writing, reading, and numerical learning), particularly for children with learning disabilities (Shamir, Korat & Fellah, 2012;Shamir & Shlafer, 2011) The educational values of e-book or mobile apps for children were widely argued. Even though young children have been reported as being able to use e-book or mobile apps on tablets and touchscreen devices such as applying required skills e.g.…”
Section: Mobile Apps and Emergent Literacymentioning
confidence: 99%